Socio-emotional Readiness of Pre–primary Students - Chandra, Reetu (THE PRIMARY TEACHER, 2017)
Early childhood is a period that lays the foundation for later development. Studies indicate that children, who attend pre–primary education programme, are likely to have better learning ability at the age of six years than those who do not. Besides, they adjust better in the school set-up socially and emotionally, which in educational terms, is referred to as ‘school readiness’. On the contrary, children, who do not attend a pre–primary education programme, may not be socially and emotionally ready to start formal school education, and eventually, drop out. Thus, ensuring a child’s socio-emotional readiness is crucial. This paper tries to assess the socio-emotional readiness of pre–primary students, studying in eight Municipal Corporation of Delhi (MCD) schools. One hundred and seventy-six pre–primary students were surveyed as part of the study. It was found that both experimental and control group students had low socio-emotional readiness in all five components — self-concept, self-control, controlling emotions, approach to learning and interactions with others. The study also tries to identify gaps in the socio-emotional readiness levels of the students and offer ways to address them.